2022
DOI: 10.3389/fnut.2021.742737
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Food Frequency Questionnaire for Assessing Habitual Intake of Free Sugar Among Children in Saudi Arabia

Abstract: The World Health Organization emphasizes the urgency to assess and limit the intake of free sugar (FS) among individuals in order to prevent several non-communicable diseases. However, data regarding intake of FS are lacking in Saudi Arabia and in the Middle East. A reliable valid tool is needed to assess children's habitual intake of FS. Thus, we aimed to develop and validate a food frequency questionnaire (FFQ) that assesses children's habitual intake of FS in Saudi Arabia. In this cross-sectional study, 424… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Consistent with findings from the present analysis of the InFANT FFQ, the 41-item FFQ developed by Hunsberger et al revealed that free sugars intakes estimated from the FFQ and 24-h recalls were highly correlated, but the FFQ underestimated free sugars intake [ 26 ]. In contrast, Mumena et al [ 25 ] found that their FFQ overestimated free sugars intakes relative to the 24-h recalls, and there was a low correlation between free sugars intakes estimated from the two methods. The overestimation in Mumena et al [ 25 ] was likely due to the inclusion of a comprehensive list of free-sugars-containing food sources (12 food groups and 41 food items) as the FFQ was purpose-designed to capture free sugars intake.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Consistent with findings from the present analysis of the InFANT FFQ, the 41-item FFQ developed by Hunsberger et al revealed that free sugars intakes estimated from the FFQ and 24-h recalls were highly correlated, but the FFQ underestimated free sugars intake [ 26 ]. In contrast, Mumena et al [ 25 ] found that their FFQ overestimated free sugars intakes relative to the 24-h recalls, and there was a low correlation between free sugars intakes estimated from the two methods. The overestimation in Mumena et al [ 25 ] was likely due to the inclusion of a comprehensive list of free-sugars-containing food sources (12 food groups and 41 food items) as the FFQ was purpose-designed to capture free sugars intake.…”
Section: Discussionmentioning
confidence: 91%
“…In contrast, Mumena et al [ 25 ] found that their FFQ overestimated free sugars intakes relative to the 24-h recalls, and there was a low correlation between free sugars intakes estimated from the two methods. The overestimation in Mumena et al [ 25 ] was likely due to the inclusion of a comprehensive list of free-sugars-containing food sources (12 food groups and 41 food items) as the FFQ was purpose-designed to capture free sugars intake. It is worth noting that the overestimation of dietary intakes is a well-known phenomenon in FFQ development [ 18 ].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This FFQ consists of 67 food items and according to Cade et al [15], less than 100 items per FFQ would be optimal, thus this number can consider as su cient to obtain accurate data. Previous studies which develop FFQ to assess sugar intake has identi ed an almost close number of items as 64 [10] and 78 [22].…”
Section: Discussionmentioning
confidence: 99%
“…A food guide as well as a table of frequency response options were shared with mothers via WhatsApp to help in accurately estimating the portion size of foods consumed. A validated FFQ that has been designed to evaluate FS intake among Saudi children was used to investigate the top sources of FS ( 26 ). The FFQ includes 40 food items classified in 12 food groups as follows: (1) “sweetened beverages (fruit drink, soft drink, flavored milk, smoothie)”; (2) “ready to eat cereals (ready to eat cereals: lower sugar [≤ 21.2 g/100 g], ready to eat cereals: higher sugar [> 21.2 g/100 g])”; (3) “breads and rolls (yeast breads, rolls and buns)”; (4) “sweet bakery products (cake, fruit pie or cheesecake, cookies, brownies, doughnuts, biscuit, muffins, French toast, pancakes/waffles, sweet pastries)”; (5) “quick breads and bread products (croissant, pastries)”; (6) “candy (candy not containing chocolate; candy containing chocolate)”; (7) “other desserts (ice-cream, popsicle, gelatin, pudding)”; (8) “sugars (sugars in tea and coffee, honey, jam, chocolate spread, peanut butter, syrups)”; (9) “yogurt (yogurt, flavored yogurt)”; (10) “mixed dishes (pizza or burger, all varieties, Chinese food, all varieties)”; (11) “condiments and sauces (ketchup, salad dressing [ranch, blue cheese, and Italian], salad dressing: [French, BBQ, and thousand island])”; (12) “fruits (canned fruits).” Frequency of consumption were as follows: “per day (once, 2–3 times, 4–5 times, or 6 times or more)”, “per week (once, 2–4 times, or 5–6 times)”, “per month (< once or 1–3 times)”.…”
Section: Methodsmentioning
confidence: 99%